2013
DOI: 10.1039/c3ce42006j
|View full text |Cite
|
Sign up to set email alerts
|

Post-synthetic cation exchange in the robust metal–organic framework MIL-101(Cr)

Abstract: In this work an unambiguous proof of post-synthetic solventassisted cation exchange in the robust metal-organic framework MIL-101(Cr) is reported. Such substitution can alter directly the secondary building unit, which often defines the properties of the material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…Cation and linker exchange can occur in some MOFs even under mild conditions 76. 77 Carbonates could coordinate to the metal component (chromium cluster) in the MOF and displace the ligand, resulting in framework decomposition 65. 78 In addition, carbonates form hydroxides in aqueous media,79 which can destroy the MOF structure; tests with NaOH as the base for the catalytic reaction resulted in MOF decomposition,22 and aqueous NaOH has been used to digest MIL‐101‐NH 2 (Cr) 75.…”
Section: Resultsmentioning
confidence: 99%
“…Cation and linker exchange can occur in some MOFs even under mild conditions 76. 77 Carbonates could coordinate to the metal component (chromium cluster) in the MOF and displace the ligand, resulting in framework decomposition 65. 78 In addition, carbonates form hydroxides in aqueous media,79 which can destroy the MOF structure; tests with NaOH as the base for the catalytic reaction resulted in MOF decomposition,22 and aqueous NaOH has been used to digest MIL‐101‐NH 2 (Cr) 75.…”
Section: Resultsmentioning
confidence: 99%
“…21 Not all structures can be desolvated as MM-BTT, but the metal sites in many other SBUs typically feature bound solvent molecules. 27 28 In another case of partial solvation, the exchangeable di-zinc sites in NTU-101-Zn 29 [Zn 2 (TADYDI)(DMF) 3 ] n and {[Zn 2 (BDCPPI)(DMF) 3 ]Á7DMFÁ5H 2 O} n contain a Zn 2+ ion held to the framework by only three bonds, with its remaining coordination sphere filled by three solvent molecules. 30 The material {[Zn(…”
Section: Which Sbus Undergo Cation Exchange?mentioning
confidence: 99%
“…MIL-101(Cr) has been chosen as starting material owing to its high surface area, its high hydrogen uptake at 77 K and outstanding chemical stability. 12 Although MIL-101 has been suggested not to be a possible starting material for solvent-assisted linker exchange (SALE), 13 we have recently shown that post-synthetic cation exchange is possible in the same material, 14 suggesting that post-synthetic linker exchange may also be possible. 2-Br-BDC and 2-NH2-BDC (for molecular structures, see Supporting Information, Figure S1) were chosen as substitute linkers for their highly electronegative functional groups that may allow for different types of interactions with the adsorbent hydrogen molecules: while the -Br functionality is highly polarizable and can thus partake in strong van der Waals interactions, the -NH2 functionality may allow for more specific interactions through its lone electron pair or via dihydrogen bonding.…”
mentioning
confidence: 99%